Efficacy of proprietary Lactobacillus casei for anti-tuberculosis associated gastrointestinal adverse reactions in adult patients: a randomized, open-label, dose–response trial. Issue 1 (9th December 2019) - Lin, Song; Zhao, Shanliang; Liu, Jiahong; Zhang, Jianwen; Zhang, Chao; Hao, Haibo; Sun, Yuxia; Cai, Jing; Yang, Yang; Ma, Yan; Li, Yuanyuan; Wang, Jinyu; et al.
Abstract : Anti-tuberculosis (TB) drugs can induce a series of gastrointestinal adverse events, which can seriously affect patients' quality of life and may lead to treatment failure. Abstract : Anti-tuberculosis (TB) drugs can induce a series of gastrointestinal adverse events, which can seriously affect patients' quality of life and may lead to treatment failure. Studies have shown that probiotics treatments can improve antibiotic-induced gastrointestinal symptoms. In this randomized, open-label, dose–response clinical trial, we investigated the preventive effects of Lactobacillus casei on anti-TB-induced gastrointestinal adverse events. In total, 429 adult patients who underwent intensive-phase anti-TB therapy were included and randomly assigned to consume one bottle of L. casei of per day (low-dose group, n = 142), two bottles of L. casei per day (high-dose group, n = 143), or no intervention (control group, n = 144) for 2 months. Each bottle of L. casei contained 10 billion colony-forming units of live L. casei . Patients' daily gastrointestinal symptoms were recorded during the intervention period. After 2 months of L. casei consumption, 397 patients had completed the intervention. Both the high and low dose L. casei groups (37.6% and 29.4%, respectively) had lower incidences of anti-TB-associated total gastrointestinal adverse events than the control group (50.0%). The high and low dose L. casei groups (3.5 d and 5.8 d, respectively) also had shorter duration anti-TB-associated adverse gastrointestinal symptoms than the control group (6.2 d). Regarding individual symptoms, the higher L. casei dose resulted in a lower incidence of vomiting and appetite loss. Similar dose-dependent protective effects of L. casei were observed regarding the duration of vomiting and appetite loss. These findings indicated that daily L. casei consumption prevented anti-TB-associated gastrointestinal adverse events. This trial was registered at the Chinese Clinical Trial Register (ChiCTR-IOR-17013210).